Transmission loss of nap cores made with cotton (CO) and polylactic acid (PLA) for application in lightweight construction. (2020) - Stehle, Franziska; Herrmann, Axel S.
Abstract: This work characterises the acoustic properties and the porosity of composites made with cotton (CO) and polylactic acid (PLA) fibres for application in lightweight construction (i.e. tiling for offices; dividing walls in offices booths). The impedance tube was used to test frequencies from 50 to 1600 Hz. The composite was tested with two different shapes (two-dimensional and with nap cores) and two different mixing ratios per weight (70/30 CO/PLA and 50/50 PLA/CO) while the production process and parameters remained the same. The results show that the transmission loss in the high frequencies was improved by the naps whereas two-dimensional composite obtain a higher transmission loss in the low frequencies.